The Influence Of Personality Traits On Cyberbullying Behaviour Among Malaysian Students - Narayanasamy, Kogilah (2019)
Bullying has existed since the dawn of humanity, but not much emphasis was placed on the issue in the early days. In recent years, the use of technology unethically had caused many undesirable social issues. One of the most worrying concern was “Cyberbullying”. Cyberbullying is an act conducted through any electronic device by an individual or group with deliberate intend to send offensive messages to cause mischief or inconvenience to others. Based on published news in The Star and NST from 2017 till 2018 there were cases of suicides and attempted suicides in Malaysia relating to cyberbullying. This research has undertaken to determine the influence of personality traits on cyberbullying behaviour. The traits investigated are Extraversion, Introversion, Neuroticism, Impulsiveness and one of the dark triad personality traits, Narcissism. In addition, the study suggests that other vital factors that act as conduit pipe for cyberbullying, are Facebook Usage, Internet Addiction, and Privacy Concern. Moreover, Selfitis, a trait that many users are showing nowadays, is also hypothesised to moderate the relationship between Narcissism and Cyberbullying Behaviour. This study used a structured questionnaire via the purposive sampling method. The questionnaire survey was divided into two sections. A nominal scale was employed to obtain the respondents’ background information. A total of 574 questionnaires were collected via online, mainly focusing on the age range of 16–35 years old. The response rate was 91.21% with 523 completed questionnaires; a sample size that was considered usable for this study.